ANALISIS MEDAN MAGNET ELF TERHADAP NILAI pH IKAN DALAM PROSES PENGAWETAN IKAN BANDENG (Chanos chanos) - Nurhasanah Nurhasanah; Sudarti Sudarti; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2018)
Abstract The ELF (Extremely Low Frequency) magnetic field is a spectrum of electromagneticwaves that located at frequencies less than 300 Hz and classified as non ionizingradiation. The ELF magnetic field is utilized in many case, one of them in the case offood, it is because the magnetic field can be applied to inactivate pathogenicmicroorganisms that cause food easily damaged or rotten. One of the factors in food thatcan be a reference related to microbial growth is pH (Hydrogen potential). This studyaims to determine the effect of ELF magnetic field exposure in the preservation of milkfishto the pH value. This study involved 21 samples of fresh milkfish, with the selection ofcontrol and experiment class. The experimental sample was exposed to an ELF magneticfield with an intensity of 730.56 μT and 877.37 μT with exposure time of 2 x 30 and 2 x45 minutes. pH measurement using pH meter. The result of this research is ELF magneticfield exposure affects the pH value of milkfish, which can inhibit the increment of pHvalue. The effective dose in inhibiting pH value is ELF magnetic field exposure with730.56 μT during 2 x 30 minutes. Keywords: Magnetic Field Extremely Low Frequency (ELF), Preservation, Milkfish